2021
DOI: 10.1186/s12957-021-02320-4
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative oxaliplatin-based hyperthermic intraperitoneal chemotherapy: an effective and safe palliative treatment option for colorectal cancer with peritoneal metastasis

Abstract: Background The prognosis of patients with colorectal cancer and peritoneal metastasis (CRC-PM) after incomplete cytoreductive surgery (CRS) or palliative surgery is poor. Novel and effective therapies are urgently needed. This study aimed to assess the effects of palliative postoperative hyperthermic intraperitoneal chemotherapy (HIPEC) in patients with CRC-PM. Methods This retrospective study included patients with CRC-PM at the First Affiliated H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…However, the most common grade 3–4 side effects with HIPEC were haemorrhage, digestive leakage, and haematological adverse events, and no neurotoxicity appeared to be observed ( Goéré et al, 2020 ; Quénet et al, 2021 ). However, a retrospective study suggested that postoperative oxaliplatin-based HIPEC might contribute to improve ascites-free survival, but is accompanied by high neurotoxicity ( Sun et al, 2021 ). Therefore, it requires further studies with large samples to observe the antitumor activity and OIPN of HIPEC oxaliplatin.…”
Section: Oxaliplatin Pharmacokinetics and Oipnmentioning
confidence: 99%
“…However, the most common grade 3–4 side effects with HIPEC were haemorrhage, digestive leakage, and haematological adverse events, and no neurotoxicity appeared to be observed ( Goéré et al, 2020 ; Quénet et al, 2021 ). However, a retrospective study suggested that postoperative oxaliplatin-based HIPEC might contribute to improve ascites-free survival, but is accompanied by high neurotoxicity ( Sun et al, 2021 ). Therefore, it requires further studies with large samples to observe the antitumor activity and OIPN of HIPEC oxaliplatin.…”
Section: Oxaliplatin Pharmacokinetics and Oipnmentioning
confidence: 99%
“…This has not been clearly evaluated in the literature, and current clinical practice at most institutions favour initial MMC-HIPEC to facilitate initial oxaliplatin-based systemic chemotherapy to reduce the dose-limiting risk of neurotoxicity. 115,117 Oxaliplatin HIPEC. The use of oxaliplatin-HIPEC has been controversial in the CRC setting.…”
Section: Evidence For Hipec After Debulking Surgerymentioning
confidence: 99%
“…The combination of two or more anti-tumor drugs can synergistically inhibit the growth of peritoneal masses (Yang et al, 2018 ). Oxaliplatin has proved to be highly effective for the palliative in-situ treatment of metastatic peritoneal cancer (Sun et al, 2021 ). Norcantharidin (NCTD), a demethylated derivative of zebularine, is a natural product with potent anti-tumor effects against multiple cancers, including liver cancer (Liu et al, 1995 ; 2020 ).…”
Section: Introductionmentioning
confidence: 99%